The Relationship Between Poverty and Economic Growth in Developing Countries: An Empirical Analysis and Policy Implications - Vinandri Hapsari; Elmiwati (Return : Study of Management, Economic and Bussines, 2026)
The relationship between poverty and economic growth remains a central debate in development economics, as many developing countries experience high growth yet still face persistent poverty, raising questions about the effectiveness of growth in reducing poverty. This study aims to empirically analyze the relationship between poverty and economic growth in developing countries, identify factors influencing the effectiveness of growth in reducing poverty, and examine the roles of income distribution, institutional quality, and sectoral composition. The research employed panel data from 24 developing countries for the period 1997-2022 using System Generalized Method of Moments (SGMM) and Two-Stage Least Squares (2SLS). The findings show a strong inverse link between poverty rates and economic growth. Results indicate that poverty levels can be lowered by 0.68% for every 1% increase in GDP per capita growth. However, institutional quality and income distribution have a significant impact on how well growth reduces poverty. Sub-Saharan African countries face difficulties in transforming growth into poverty reduction compared to East Asia and Pacific countries. In conclusion, sustained growth above 3.2% annually, combined with equitable income distribution, strong governance, and agricultural sector development, is essential for maximizing poverty reduction. This study recommends inclusive growth strategies with strengthening distribution systems and investments in education and infrastructure sectors.